The effect of urinary ıncontinence awareness and attitudes of patients applying to urology outpatient clinic - DURMUŞ İSKENDER, Mahinur; GÜL, Sıla (Pamukkale University, 2023)
Purpose: This study was conducted to determine the effect of urinary incontinence on the awareness and attitudes of patients applying to urology outpatient policlinics. Materials and methods: The data of this descriptive and cross-sectional study were collected between 07/09/2023-08/10/2023 with Personal Information Form, Urinary Incontinence Awareness Attitude Scale data collection tools from 180 people who applied to urology outpatient clinic by face-to-face interview method. Data were analyzed with the SPSS 25.0 package program. In all analyses, p
Keywords: 3. Good health